Pengaruh Dewan Komisaris Independen, Kepemilikan Institusional Dan Corporate Social Responsibility Terhadap Kinerja Perusahan - Muhammad Ilyas Ramadan; Ayumi Rahma (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
This study aims to reveal the influence of an independent board of commissioners, institutional ownership, and corporate social responsibility on company performance. This study was conducted on non-cyclical consumer companies listed on the Indonesia Stock Exchange between 2020 and 2024. Hypothesis testing was conducted using Eviews 13. A sample of 12 companies was selected using a purposive sampling technique and several criteria appropriate to the research needs. The test results revealed that the independent board of commissioners, institutional ownership, and corporate social responsibility variables simultaneously had a significant effect on company performance. Partially, institutional ownership had a negative effect on company performance. Meanwhile, the independent board of commissioners and corporate social responsibility had no effect on company performance